Breast carcinoma in sclerosing adenosis: a clinicopathological and immunophenotypical analysis on 206 lesions. Issue 6 (7th February 2018) - Yu, Bao-Hua; Tang, Shao-Xian; Xu, Xiao-Li; Cheng, Yu-Fan; Bi, Rui; Shui, Ruo-Hong; Tu, Xiao-Yu; Lu, Hong-Fen; Zhou, Xiao-Yan; Yang, Wen-Tao
Abstract : Aims: To fully elucidate the clinicopathological features of breast carcinoma in sclerosing adenosis (SA-BC). Methods: Clinical and histological characteristics of 206 SA-BCs from 180 patients were retrospectively evaluated. Immunohistochemical phenotype was examined. The clinicopathological relevance of the topographical pattern of SA-BCs was analysed. Results: Overall, up to 46 patients (25.6%) had contralateral cancer, either SA associated or not. Of 99 cases who underwent core needle biopsy (CNB), 36 were underestimated as adenosis or atypical ductal hyperplasia at CNB, 5 invasive cases were misinterpreted as in situ carcinomas, whereas 4 ductal carcinoma in situ (DCIS) cases were overdiagnosed as invasive carcinoma. Microscopically, 163 tumours were in situ, including 136 DCIS, 19 lobular carcinomas in situ (LCIS) and 8 mixed DCIS/LCIS; of these carcinomas in situ (CIS), 37 had microinvasion. The DCIS group exhibited low, intermediate and high grades in 53.7%, 34.6% and 11.8% of cases, respectively, mostly with solid (43.4%) or cribriform (41.9%) pattern. Forty out of 43 invasive cases were invasive ductal carcinoma (IDC), mostly DCIS predominant. Immunophenotypically, luminal A phenotype was identified in 55.1%, 63.2% and 45.0% of DCIS, LCIS and IDC cases, respectively. Topographical type A group (carcinoma being entirely confined to SA, n=176) was characterised by smaller size, less invasiveness, lower grade and more frequency of luminal A immunophenotype compared with type B group (≥ 50% but not all of the carcinomatous lesion being located in SA, n=30) (all P<0.05). Conclusions: CIS, especially non-high-grade DCIS, represents the most common variant of SA-BC, and luminal A is the most predominant immunophenotype. CNB assessment might be challenging in some SA-BCs. The topographical pattern has great clinicopathological relevance. Careful evaluation of the contralateral breast and long-term follow-up for patients with SA-BC is necessary given its high prevalence of bilaterality.